Pengaruh Gaya Kepemimpinan dan Literasi Digital terhadap Kinerja Pegawai Dinas Pariwisata, Kebudayaan, Kepemudaan dan Olahraga Kabupaten Sumedang - Mohamad Riza Pratama; Kusuma Agdhi Rahwana; Gian Riksa Wibawa (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to determine the influence of leadership style and digital literacy on the performance of Sumedang Regency Tourism, Culture, Youth and Sports Department employees. The method used was a quantitative approach with a research sample of 43 respondents, namely all employees of the Tourism, Culture, Youth and Sports Department of Sumedang Regency. The data used is primary data and secondary data. The data testing technique used in this research uses validity tests, reliability tests and classical assumption tests. The analytical tool used in this research is multiple linear regression analysis using SPSS version 26. The research results show that simultaneously Leadership Style and Digital Literacy have a significant effect on employee performance. Partially Leadership Style has a significant effect on employee performance. Partially, Digital Literacy has a significant effect on employee performance.